Multicultural Education In Social Perspective - Afi Parnawi; Abdullah Idris (International journal of technology and education research, 2023)
This article discusses the concept of multicultural society from a sociological perspective, using the Indonesian state as a historical aggregator of diverse ethnic groups, nations, religions, and beliefs as a case study. There are times when variety in Indonesia leads to conflict, but there are other instances where the nation's diversity serves as a source of strength to shield each other from being crushed by the progress of time. Equipped to understand multiculturalism is not limited to intellectuals or community leaders; rather, knowing multiculturalism is required at all levels, layers, and tiers of society. As a result of the media's exaggeration of SARA (ethnicity, religion, race, and inter-group) concerns, the Indonesian populace is currently extremely vulnerable to catastrophic social changes. To prevent a recurrence of